MiR-137 Deficiency Causes Anxiety-Like Behaviors in Mice - Yan, Hai-Liang; Sun, Xiao-Wen; Wang, Zhi-Meng; Liu, Pei-Pei; Mi, Ting-Wei; Liu, Cong; Wang, Ying-Ying; He, Xuan-Cheng; Du, Hong-Zhen; Liu, Chang-Mei; Teng, Zhao-Qian (Frontiers in Molecular Neuroscience, 2019)
Anxiety and depression are major public health concerns worldwide. Although genome-wide association studies have identified several genes robustly associated with susceptibility for these disorders, the molecular and cellular mechanisms associated with anxiety and depression are largely unknown. Reduction of microRNA-137 (miR-137) level has been implicated in the etiology of major depressive disorder. However, little is known about the in vivo impact of the loss of miR-137 on the biology of anxiety and depression. Here we generated a forebrain-specific miR-137 knockout mouse line, and showed that miR-137 is critical for dendritic and synaptic growth in the forebrain. Mice with miR-137 loss-of-function exhibit anxiety-like behavior, and impaired spatial learning and memory. We then observe an elevated expression of EZH2 in the forebrain of miR-137 knockout mice, and provide direct evidence that knockdown of EZH2 can rescue anxious phenotypes associated with the loss of miR-137. Together our results suggest that loss of miR-137 contributes the etiology of anxiety, and EZH2 might be a potential therapeutic target for anxiety and depressive phenotypes associated with the dysfunction of miR-137.